Microbiome Structure Analysis of Oil Palm Pollinator Elaeidobius kamerunicus (Coleoptera; Curculionidae) - Arina Amalia Putri; Maria Sugiharti; Alfred Michael; Anja Meryandini; Antonius Suwanto (HAYATI Journal of Biosciences, 2023)
The pollination of oil palm by Elaeidobius kamerunicus leads to an increase of over 70% in countries such as India, Malaysia, and Indonesia. The impact of insect-microbiome interactions on the pollination activity and fitness of E. kamerunicus is unknown. Our study aimed to gain insight into the bacterial communities of E. kamerunicus from two different sites with high and low fruit set percentages, using culturable and Terminal Restriction Fragment Length Polymorphism (T-RFLP) analysis. Our result revealed distinctive T-RFs profiles in E. kamerunicus from two different sites. Additionally, the culturable approach showed that some of this microbiome were found only in the weevil population from the high fruit set site. Our findings suggest that these bacteria could contribute to the fitness of E. kamerunicus, leading to a higher fruit set in oil palm plantations.